OPTIMIZATION OF NONCONVENTIONAL UV EMISSION PILLAR OF THE AUTONOMOUS MOBILE PLATFORM THROUGH STRUCTURAL ANALYSISCS - Mihail Aurel Titu; Daniel Balc; Emanuel Balc (Nonconventional Technologies Review)
The present study is dedicated to a meticulous optimization process of the UV emission pole on an autonomous mobile platform, employing structural analysis and the finite element analysis program ANSYS. Through sophisticated simulations, a comprehensive evaluation of the forces and stresses to which the pole is subjected under diverse operational conditions is meticulously executed, thereby facilitating the identification of critical junctures and potential enhancements pertaining to the geometry or materials employed. The finite element analysis conducted in ANSYS offers a precise modus operandi for modelling the structural behaviour of the pole. This method allows for the simulation of authentic operating conditions, thereby providing a comprehensive framework for evaluating the efficacy of the extant project. Furthermore, the finite element analysis facilitates the visualization of deformations and stress distributions, thereby yielding invaluable insights for the optimization endeavour. Through the implementation of this advanced analytical program, the study proffers a scholarly and technical approach toward comprehending and refining the performance of the UV emission pole. This integrated research methodology proclaims noteworthy contributions to the realm of technological development, ensuring a robust foundation for design and optimization determinations within the domain of autonomous mobile platforms.